2018
DOI: 10.1136/postgradmedj-2017-135397
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating leptin levels and multiple sclerosis: a systematic review and meta-analysis

Abstract: Overall, our study suggests that patients with MS have a significantly higher leptin level than in healthy controls. Further mechanism studies and longitudinal large cohort studies are still needed to further reveal the role of leptin in the pathogenesis of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
(11 reference statements)
0
19
1
Order By: Relevance
“…[ 39 ] So leptin activates mTOR. Leptin was not found helpful as an MS activity biomarker in one study [ 8 ] but, in a meta-analysis, higher serum leptin levels were found in MS patients than the control group, [ 7 ] suggesting leptin as a biomarker. The role of leptin could not be demonstrated in a study conducted with naive patients with clinically isolated syndrome and RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] So leptin activates mTOR. Leptin was not found helpful as an MS activity biomarker in one study [ 8 ] but, in a meta-analysis, higher serum leptin levels were found in MS patients than the control group, [ 7 ] suggesting leptin as a biomarker. The role of leptin could not be demonstrated in a study conducted with naive patients with clinically isolated syndrome and RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is a well-known fact that women are more prone to develop many autoimmune diseases including MS, with sex ratios ranging from 9:1 for systemic lupus erythematosus (SLE) to a more modest 2:1 or according to more recent data 3:1 for MS, with rheumatoid arthritis (RA) having a ratio somewhere in between. 28 For both SLE and RA patients, serum levels of leptin appear to be increased 29 as is also the case with MS. 7 Since women have higher levels of leptin than men, even at the same BMI, it is attractive to propose elevated leptin as a possible explanation for the observed sex difference in disease occurrence. 30 In the present study, women had about five times higher median leptin concentrations compared to men, providing an example of a sex difference that no other known MS risk factor has shown, giving support to the notion that leptin may be of etiological importance.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier case–control studies on leptin in patients with established MS have shown conflicting results, but according to a recent meta-analysis, leptin levels are higher among those with MS. 7 There are also studies indicating a role for leptin in induction of experimental autoimmune encephalomyelitis (EAE), the animal model of MS, where leptin deficient mice failed to develop EAE unless leptin was systemically administered. 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations